PARE0019 Patient Perspectives on Footwear in Rheumatoid Arthritis – A Patient-Led Qualitative Study. (9th June 2015) - de Souza, S.; Lempp, H.
Abstract : Background: As a patient with rheumatoid arthritis (RA) I have encountered others who complain about problems with footwear as a result of RA affecting their feet. They experience lack of recognition of their problems by healthcare professionals. Recent studies, led by podiatrists, support these views of patients; two focused solely on therapeutic footwear. Therefore, I decided to tackle this important topic and systematically investigated patients' perspectives first-hand. Objectives: To explore the perspectives of rheumatoid arthritis patients in relation to footwear as part of a service evaluation. Methods: A convenience sample of adult participants who met the inclusion criteria (diagnosis of RA and ability to communicate in English) were recruited by clinic staff from a rheumatology outpatient clinic in London. Eight females and one male (aged 27-68 years, disease duration 4-46 years and of diverse ethnic background) agreed to take part in two focus groups conducted by the lead patient researcher. All information provided was recorded and transcribed verbatim. The shared experiences between the researcher and patients generated an instant rapport and a richness of data. A random sample of four participants from the focus groups verified the authenticity of the transcripts, thus adding to their credibility. Qualitative computer software was used to assist with systematic coding and the resultant themes were cross-checked by the co-researcher. This helped negate any potential patient-bias by the lead researcher and added to the trustworthiness of the qualitative data. Results: Six closely interlinked themes constituted the analytical framework under which the data are presented: (1) self-conscious about appearance of feet, e.g. feel uncomfortable about feet being viewed by others; (2) footwear/clothing choice restricted, e.g. having to wear running shoes all the time which can only match casual wear; (3) lack of appropriate shoes available, e.g. finding shoes of sufficient width and depth; (4) cost of suitable footwear, e.g. running shoes recommended by the podiatrist are expensive; (5) lack of empathy from clinic staff, e.g. women advised to not wear heels when they constitute part of their identity; and (6) expect to receive footwear advice from the rheumatology team, e.g. where to buy comfortable shoes. The sole male participant was unaffected by themes (1) and (2). No differences were identified across age, ethnicity or disease duration. Conclusions: The impact RA has on feet seems to make women feel self-conscious and limits their choice of footwear styles and accompanying clothing choices thus affecting how they would wish to express themselves. Shoes recommended by healthcare professionals appear to be viewed as unattractive, expensive and often inappropriate for work and social occasions. Patients expect greater insight from healthcare professionals about their needs and guidance on appropriate footwear from the rheumatology team. Acknowledgements: We are grateful to James Galloway and Carron Congreves for patient recruitment, Patience Duffort for transcription services and to the patients who participated for sharing their views. Disclosure of Interest: None declared